Detection of childhood developmental disorders, behavioral disorders, and depression in a post-earthquake setting - Yogi Prawira; Intan Tumbelaka; Ali Alhadar; Erwin Hendrata; Renno Hidayat; Dave Anderson; Trevino Pakasi; Bernie Endyarni; Rini Sekartini (Indonesian Pediatric Society, 2011)
Background Disasters, including earthquakes, may strike abruptlyÂ without warning. Children may develop psychological damageÂ resulting from experiencing an overwhelmingly traumatic event.Â They may feel very frightened during a disaster and demonstrateÂ emotional and behavioral problems afterwards.Objective To evaluate the presence of developmental disorders,Â behavioral disorders, and depression in children after theÂ earthquake at Padang and Pariaman on September 30th, 2009.Methods This was a crossô€˜sectional study using the developmentalÂ pre screening questionnaire (KPSP), Pediatric SymptomsÂ Checklist-17 (PSC-17), and Child Depression Inventory (CDI) inÂ children after the Padang and Pariaman earthquake (SeptemberÂ 30th, 2009), in Sungai Limau and Sungai Geringging District,Â Pariaman Region, West Sumatera. Our study was conductedÂ October 15th to November 28th, 2009.Results There were 172 children screened using the KPSP. Forty-two (25%) children scored 7ô€˜8 (reason for concern), 18 (10%)Â children scored <7 (suspected to have a developmental disorder),Â and the remainder scored as developmentally appropriate.Â Behavioral disorder screening was perfonned in 339 childrenÂ using the PSCô€˜ 17. Internalizing disorder alone was suspected inÂ 58 (17%) children, externalizing disorder alone in 26 (7.7%), andÂ attentionô€˜defidt disorder alone in 5 (1.5%). Eight (2.4%) childrenÂ were suspected to have both internalizing and attentionô€˜defidtÂ disorders, 4 (1.2%) children externalizing and attentionô€˜defidtÂ disorders, 22 (6.5%) children internalizing and externalizingÂ disorders, and 15 (4.4%) children all three disorders. From 4 9Â children who underwent depression screening using CDI, 15(30.6%) children were suspected to have depression.Â Conclusion After the Padang and Pariaman earthquake, weÂ found 10% of subjects screened were suspected of having a developmental disorder. The most connnonbehavioral disorder found was internalizing disorder. Possible depression was found in 30.6% of children surveyed. Traumatized children are at riskÂ for developing post traumatic stress disorder.Â 2011;5' :133-7].Â